Birth Pleasure: Meanings, Politics, and Praxis - Berger Bolaza, Elisabeth (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
Little research has directly focused on the spectrum of pleasure experienced in birth, which until now has lacked a scholarly description or definition. In this article, I present the concept of birth pleasure and offer an introduction and preliminary definition synthesized from published experiential accounts, existing research and scholarship, and relevant lay literature. Through an intersectional and matricentric feminist lens, I offer implications of including birth pleasure in birth justice praxis.